Management Strategies in Internationalizing the Mandarin Language - Chen Limeng; Furkan, Lalu Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2025)
Mandarin, as the Chinese language, has attracted billions of people to use it as a communication tool in written and spoken forms at the international level. China has afforded various strategies to foster the development of the language worldwide. This study aimed to investigate the management strategies applied by the Chinese Government and the challenges encountered while promoting Mandarin as a global language. Employing qualitative study with library research as the approach, the researcher collected data from various credible sources to measure the quality of the findings. Content analysis was conducted deductively based on the existing data, in which the researcher commenced categorizing the relevant resources and finalized the findings by interpreting and concluding them. The result showed that the Chinese Government employs three primary management strategies to globalize the language: Promoting the Mandarin language through education, cultural exchange, and global trading. Some challenges were also identified, such as linguistic barriers, political and diplomatic challenges, and limited integration in educational systems.